ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA MELALUI PENERAPAN ASESMEN PORTOFOLIO PADA PEMBELAJARAN FISIKA - Utami, Kitri Mipa; Siahaan, Parsaroan; Purwanto, Purwanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Portfolio assessment is one of a kind that being advised by 2013 curriculum. It is included in alternative assessing which can improve students’ comprehension based on the facts (Gunay, A. 2014). However, the portfolio assessment is still rarely being used by teachers since they think that it is hard to do. This research aims to analyse students’ abilities in cognitive field of Understanding towards mechanical fluid subject. This Understanding covers seven cognitive process that occur in taxonomy Bloom’s-revision which are: interpreting, giving example, summarizing, concluding, comparing and explaining. The participants of this research are students from second grade in a high school that located in Bandung which used 2013 curriculum. The design of this research is using Nonequivalen Control Group Design. The result of this research shows that there is a significant difference towards the improvement of concept comprehension towards mechanical fluid subject between experimental class and control class. Keywords: Portfolio Assessment, Understanding, Mechanical Fluid.